Conformity and resistance to hegemonic masculinity in selected novels of D.H Lawrence - Michael, Angelina Subrayan (2016)
This thesis focuses on the critical discussion on masculinity studies in the classic fictions of D.H Lawrence. Drawing on narrative data from a collection of four novels of Lawrence, this study examines how and why hegemonic masculinity is conformed and resisted among working-class men in gendered relationships. More specifically, the analysis focuses on how the same individual can negotiate, reject and align himself with the hegemonically dominant ideology of ‘tough’ masculinity and how he integrates a range of discursive strategies which help maintain manliness when dominant masculinity is at stake within his household. The effects of social practices and socio-historical context in which Lawrence wrote these novels are also examined. Since the novels selected are related to Lawrence’s own life experiences, the author’s perspective on masculinity is also examined. The novels selected for analysis are Sons and Lovers (1913), The Rainbow (1915), The Lost Girl (1920) and Aaron’s Rod (1922). The study utilises Connell’s theory of Hegemonic masculinity and, Wetherell and Edley’s framework on the various ways in which men negotiate their masculinity to create identity positions. The aim of the study is to examine how and why the same men in their relationship with women negotiate their masculinities by positioning themselves in various ways at different times. The study explores three distinctive masculinities that do not represent fixed character types, but occupy complex subject positions which reflect constant shifting of meanings and changes in masculine identities among the male protagonists. The discursive paths taken by the male characters are analysed based on Wetherell and Edley’s notion of the three identity positions which are the Heroic position that aligns to Connell’s notion of hegemonic masculinity and two other types of subordinate masculinities which are the Ordinary man and the Rebellious man who reject hegemonic masculinity. Foucault’s notion of self formation is used as a guide in this study. As such, this thesis sees the novels as advocating a postmodern position featuring multiple discourses which deconstruct the traditional concepts of hegemonic masculinity, but do not produce a new model of ideal manhood in its place. The findings of the research show that men follow appropriate social codes that are absorbed through socially constructed norms. Malecontrolled hierarchy family structure stresses the separation of lives, women work inside the home and men work outside. The findings also indicate that at some point in their lives, these men do negotiate their dominant masculine identity to construct themselves to become reasonable human beings. Lawrence portrays negative and positive example of marriages. This study may provide deeper insights into literary discourse that are essential for educators and social researchers to look beyond texts through the lens of multiple masculinities. Balanced information in the components of research on gender is necessary since the behaviour of most men is often misunderstood and society expects certain male stereotypical traits from them which are considered to be ideal.